The COVID-19 pandemic and mental health in pregnant women: A review article - Arzamani, Niloufar; Soraya, Shiva; Hadi, Fatemeh; Nooraeen, Sara; Saeidi, Mahdieh (Frontiers in Psychiatry, 2022)
COVID-19 pandemic has negative effects on physical and mental health. These significant effects are more seen in some vulnerable populations such as pregnant women. Physiological and psychological perinatal changes per se can place pregnant women at higher risk for mental health problems such as anxiety and depression. During the outbreak of Coronavirus disease, pregnant women have experienced psychological problems like fear, anxiety, and depression more than past. The mental health of pregnant women is considerable in many aspects. Mental health problems may reduce compliance to effective preventive behaviors, provide unhealthy coping mechanisms, cause inadequate care during childbirth, and have negative effects on the prognosis of pregnancy and fetal development. Given the importance of mental health of pregnant women in fetus, child, family, and community health, the purpose of this review was to investigate the available literature on the impact of the Covid-19 pandemic on mental health in pregnant women and provide some recommendations to improve mental health in them. It also shed some light on providing mental health services for women during pregnancy and can be used by health professionals and policymakers.